The Effect of Domain Responsiveness on Inpatient Satisfcation in Inpatient Community Health Centers in 2017 (Data Analysis of Responsiveness in Risnakes 2017) - Ayu Tyas Purnamasari; Pujiyanto (JUMP Health (Journal of Ultimate Public Health), 2020)
Background: Community health centers have a role as gatekeepers within a healthcare system, even so, the utilization rate of inpatient community health centers was lower than those of government hospitals and private hospitals in 2015-2017. The low utilization rate of the inpatient community health centers might be caused by several dissatisfied patients and the low quality of the healthcare in terms of medical and nonmedical (responsiveness) aspects. Therefore, this study aims to find out the effect of responsiveness on patient satisfaction. Method: This study was using the dataset which was obtained from Healthcare Workforce Research data in 2017 from The Health Research and Development Agency regarding responsiveness in inpatient community health. The data was analyzed by using Structural Equation Modeling (SEM). Results: The domains of responsiveness consisting of dignity (t-values = 2,23), communication (t-values = 3,40), prompt attention (t-values = 2,64), quality of basic amenities (t-values = 8,37), and access to social support (t-values = 2,20) affected the patient satisfaction. Conclusion: The overall inpatient satisfaction is affected by nonmedical aspects (responsiveness) particularly the quality of basic amenities. Keywords: responsiveness, nonmedical aspects, patient satisfaction, inpatient community health centers